REPRESENTASI NILAI MORAL PADA FILM BUDI PEKERTI KARYA WREGAS BHANUTEJA (KAJIAN SOSIOLOGI SASTRA) - Melysa, Melysa Putri Ayuningtyas; puspitasari, Indah (Universitas Islam Zainul Hasan Genggong, 2024)
Movies not only entertain the audience, but also function as a means of conveying the messages they contain. Therefore, there are currently a lot of conversations about domestically and internationally produced films. The development of this movie has become a hot topic of conversation in the community. One of the movies that is currently hitting the audience is the movie 'Budi Pekerti' by Wregas Bhanuteja. The film tells the story of a guidance and counseling teacher who uses his unique technique to guide his students. Until one day, the teacher suddenly becomes a hot topic on social media. This affects his career and family. This drama genre movie presents realistic nuanced stories that are currently popular. The purpose of this research is to find out the moral values contained in the movie